Divergence and conservation of satellite DNA in the loggerhead sea turtle (Caretta caretta): a comparative cytogenomic analysis - Katerina V. Tishakova; Anastasia A. Proskuryakova; Dmitry Yu. Prokopov; Sergey A. Marchenko; Alessio Iannucci; Claudio Ciofi; Livia Tolve; Paolo Casale; Pasquale Salvemini; Natalia A. Serdyukova; Guzel I. Davletshina; Vladimir A. Trifonov; et al. (Chromosome Research, 2026)

The Potential of Cortical Electrical Stimulation for the Study of Autonomic Dysfunction in Patients with Epilepsy - A. A. Marchenko; D. V. Zhuravlev; A. A. Skalnaya; M. A. Lebedeva; M. V. Sinkin; I. S. Trifonov; A. B. Guekht (Neuroscience and Behavioral Physiology, 2026)

Mapping rat lncRNA Bdnf-as - Elizaveta V. Shaburova; Sergey A. Marchenko; Veronika B. Dneprovskaya; Anna V. Sborschikova; Dmitriy A. Lanshakov (Molecular Biology Reports, 2025)

Ultrasonic fabrication of polysaccharide capsules: Unraveling the xanthan gum-chitosan shell formation mechanism - Tatiana N. Pallaeva; Irina V. Marchenko; Polina V. Krikunova; Vladimir V. Artemov; Dmitry N. Khmelenin; Sergey N. Malakhov; Peter V. Dmitryakov; Egor A. Shramkov; Yuri M. Efremov; Peter S. Timashev; Roman A. Novikov; Olga A. Sindeeva; et al. (Carbohydrate Polymers, 2025)

Seroprevalence of anti-influenza antibodies in humans and characterization of seasonal influenza viruses isolated in Russia during the 2023–2024 flu season - Svetlana V. Svyatchenko; Nikita D. Boldyrev; Anastasia S. Panova; Natalia P. Kolosova; Kiunnei N. Shadrinova; Natalia I. Goncharova; Galina S. Onkhonova; Alina R. Muratova; Alexey V. Danilenko; Elena I. Danilenko; Andrey S. Gudymo; Natalia N. Vasiltsova; et al. (Archives of Virology, 2025)

Reverse Inhibitory Connections via GABAB-Receptors Synchronize Interictal Discharges in the Cortex - V. G. Marchenko; M. I. Zaichenko (Neuroscience and Behavioral Physiology, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

GABAB Inhibition through Feedback Is Involved in the Synchronization of Interictal Spikes in the Cortex - V. G. Marchenko; M. I. Zaichenko (Neuroscience and Behavioral Physiology, 2023)

Long-chain alkenones in the lake sediments of North-Minusinsk Valley (southern Siberia): implications for paleoclimate reconstructions - Alexander O. Bulkhin; Vladimir V. Zykov; Dmitry N. Marchenko; Marsel R. Kabilov; Olga A. Baturina; Anatoly N. Boyandin; Olesya V. Anishchenko; Denis Y. Rogozin (Organic Geochemistry, 2023)

Experimental Correction of Homeostasis Changes during Alloxan-Induced Diabetes by Implantation of Islet Cells Cultured in Fibrous TiNi-Based Scaffold - O. V. Kokorev; I. A. Khlusov; E. S. Marchenko; Yu. F. Yasenchuk; G. Ts. Dambaev (Bulletin of Experimental Biology and Medicine, 2022)

Quantitative Electroencephalography Indicators in Children with Acute Purulent Meningitis - V. B. Voytenkov; A. A. Vilnitz; N. V. Skripchenko; E. V. Ekusheva; N. A. Savelyeva; A. V. Klimkin; N. V. Marchenko; M. A. Bedova (Neuroscience and Behavioral Physiology, 2022)

Observing Wind-Forced Flexural-Gravity Waves in the Beaufort Sea and Their Relationship to Sea Ice Mechanics - Mark A. Johnson; Aleksey V. Marchenko; Dyre O. Dammann; Andrew R. Mahoney (Journal of Marine Science and Engineering, 2021)
We developed and deployed two inertial measurement units on mobile pack ice during a U.S. Navy drifting ice campaign in the Beaufort Sea. The ice camp was more than 1000 km from the nearest open water. The sensors were stationed on thick (>1 m) first- and multi–year ice to record 3-D accelerations at 10 Hz for one week during March 2020. During this time, gale-force winds exceeded 21 m per second for several hours during two separate wind events and reached a maximum of 25 m per second. Our observations show similar sets of wave bands were excited during both wind events. One band was centered on a period of ~14 s. Another band arrived several hours later and was centered on ~3.5-s. We find that the observed wave bands match a model dispersion curve for flexural gravity waves in ~1.2-m ice with a Young’s modulus of 3.5 GPa under compressive stresses of ~0.3 MPa. We further evaluate the bending stress and load cycles of the individual wave bands and their potential role in break-up of sea ice. This work demonstrates how observations of waves in sea ice using these and similar sensors can potentially be a valuable field-based tool for evaluating ice mechanics. In particular, this approach can be used to observe and describe the combined mechanical behavior of consolidated floes relevant for understanding sea ice mechanical processes and model development.

Brain Bioelectrical Activity in Children with Acute Viral Encephalitis - V. B. Voitenkov; M. V. Sinkin; N. V. Skripchenko; E. V. Ekusheva; E. Yu. Gorelick; N. V. Marchenko; A. V. Shtekleyn; M. A. Bedova (Neuroscience and Behavioral Physiology, 2021)

Comparative thermostability analysis of zoonotic and human influenza virus A and B neuraminidase - Vasily A. Evseenko; Svetlana V. Svyatchenko; Natalia P. Kolosova; Valentina L. Kovrizhkina; Vasiliy Y. Marchenko; Aleksander G. Durymanov; Natalia I. Goncharova; Alexander B. Ryzhikov (Archives of Virology, 2020)

Propagation of Endogenous Electric Fields as a Possible Mechanism of Synchronization of Interictal Spikes in the Rat Neocortex - V. G. Marchenko; M. P. Rysakova; M. I. Zajchenko (Neuroscience and Behavioral Physiology, 2019)

Analysis of Post-Operative Cognitive Dysfunction after Different Methods of Aortocoronary Bypass Surgery - G. Yu. Alekseevich; M. V. Rodikov; A. V. Marchenko; P. A. Myalyuk; G. V. Alekseevich (Neuroscience and Behavioral Physiology, 2019)

Intranasal immunization of guinea pig with trivalent influenza antigen adjuvanted by Cyclamen europaeum tubers extract - Vasily A. Evseenko; Natalia P. Kolosova; Anderi S. Gudymo; Semion V. Maltsev; Julia A. Bulanovich; Nataliya I. Goncharova; Natalia V. Danilchenko; Vasiliy Y. Marchenko; Ivan M. Susloparov; Alexander B. Ryzhikov (Archives of Virology, 2019)

Humoral immunity to influenza in an at-risk population and severe influenza cases in Russia in 2016–2017 - Tatyana N. Ilyicheva; Alexander G. Durymanov; Svetlana V. Svyatchenko; Vasily Yu. Marchenko; Ivan A. Sobolev; Anastasiya Yu. Bakulina; Natalia I. Goncharova; Natalia P. Kolosova; Ivan M. Susloparov; Olga G. Pyankova; Alexander B. Ryzhikov; Rinat A. Maksyutov (Archives of Virology, 2018)

Reintroduction of highly pathogenic avian influenza A/H5N8 virus of clade 2.3.4.4. in Russia - Vasiliy Y. Marchenko; Ivan M. Susloparov; Andrey B. Komissarov; Artem Fadeev; Nataliya I. Goncharova; Andrey V. Shipovalov; Svetlana V. Svyatchenko; Alexander G. Durymanov; Tatyana N. Ilyicheva; Lyudmila K. Salchak; Elena P. Svintitskaya; Valeriy N. Mikheev; et al. (Archives of Virology, 2017)

Effect of Tubocurarine on Large-Conductance Cationic Channels in the Inner Nuclear Membrane of Purkinje Neurons of the Rat Cerebellum - O. V. Lunko; I. V. Grushkovska; O. O. Lun’ko; S. M. Marchenko (Neurophysiology, 2016)

Highly pathogenic influenza H5N1 virus of clade 2.3.2.1c in Western Siberia - V. Y. Marchenko; I. M. Susloparov; N. P. Kolosova; N. I. Goncharova; A. V. Shipovalov; T. N. Ilyicheva; A. G. Durymanov; O. A. Chernyshova; L. I. Kozlovskiy; T. V. Chernyshova; E. N. Pryadkina; T. V. Karimova; et al. (Archives of Virology, 2016)

Synchronization and Propagation of Electrical Potentials in Neural Networks in the Cerebral Cortex - V. G. Marchenko; M. I. Zaichenko (Neuroscience and Behavioral Physiology, 2016)

Influenza A(H5N8) virus isolation in Russia, 2014 - Vasiliy Y. Marchenko; Ivan M. Susloparov; Nataliya P. Kolosova; Nataliya I. Goncharova; Andrey V. Shipovalov; Alexander G. Durymanov; Tatyana N. Ilyicheva; Lubov V. Budatsirenova; Valentina K. Ivanova; Georgy A. Ignatyev; Svetlana N. Ershova; Valeriya S. Tulyahova; et al. (Archives of Virology, 2015)

The Distribution of 137Cs, 90Sr, and 241Am in Waterbodies of Different Origins in the Belarusian Part of Chernobyl Exclusion Zone - Yu I. Bondar; R. A. Nenashev; S. A. Kalinichenko; Yu D. Marchenko; M. Dowdall; W. Standring; J. E. Brown; M. Pettersen; L. Skipperud; V. N. Zabrotski (Water, Air, & Soil Pollution, 2015)

Erratum to: Peculiarities of Microhemocirculation in the Rat Brain after Different Modes of Cold Acclimation - D. G. Lutsenko; A. V. Shilo; I. V. Sleta; V. S. Marchenko (Neurophysiology, 2014)

Molecular characterization and phylogenetics of a reassortant H13N8 influenza virus isolated from gulls in Mongolia - K. Sharshov; M. Sivay; D. Liu; M. Pantin-Jackwood; V. Marchenko; A. Durymanov; A. Alekseev; T. Damdindorj; G. F. Gao; D. E. Swayne; A. Shestopalov (Virus Genes, 2014)

Peculiarities of Microhemocirculation in the Rat Brain after Different Modes of Cold Acclimation - D. G. Lutsenko; A. V. Shilo; I. V. Sleta; V. S. Marchenko (Neurophysiology, 2014)

Prognostic Significance of Blood Brain-Derived Neurotrophic Factor (BDNF) in the Treatment of Various Functional and Organic Nervous System Diseases with Adaptol - S. A. Zhivolupov; I. N. Samartsev; A. A. Marchenko; O. V. Pulyatkina (Neuroscience and Behavioral Physiology, 2013)

Properties of Large-Conductance Cationic Channels in the Neuronal Nuclear Envelope - E. A. Fedorenko; O. V. Semenova; S. M. Marchenko (Neurophysiology, 2011)

Impact of Amyloid-β Peptide (1–42) on Voltage-Gated Ion Currents in Molluscan Neurons - E. I. Solntseva; J. V. Bukanova; E. V. Marchenko; V. G. Skrebitsky (Bulletin of Experimental Biology and Medicine, 2011)

Synchronization Mechanisms in Local Neural Networks in the Neocortex. Modeling and Experimental Studies - V. G. Marchenko; K. A. Saltykov (Neuroscience and Behavioral Physiology, 2011)

Erratum to the article “Use of Fractal Analysis for Evaluation of Liver Structure and Function in Rats In Vivo” by A. A. Olefirenko, D. G. Lutsenko, I. V. Sleta, and V. S. Marchenko, Vol. 147, No. 2, February, 2009 - A. A. Olefirenko; D. G. Lutsenko; I. V. Sleta; V. S. Marchenko (Bulletin of Experimental Biology and Medicine, 2009)

Use of Fractional Analysis for Evaluation of Liver Structure and Function in Rats In Vivo - A. A. Olefirenko; D. G. Lutsenko; I. V. Sleta; V. S. Marchenko (Bulletin of Experimental Biology and Medicine, 2009)

Will transgenic plants adversely affect the environment? - Vassili V. Velkov; Alexander B. Medvinsky; Mikhail S. Sokolov; Anatoly I. Marchenko (Journal of Biosciences, 2005)

Direction of fluid transport in the lens - L. V. Stepanova; I. Yu. Marchenko; G. M. Sychev (Bulletin of Experimental Biology and Medicine, 2005)

Intracortical Synchronization of Epileptic Discharges at Different Stages of Ultrastructural Rearrangements in a Completely Neuronally Isolated Area of Rat Neocortex - V. G. Marchenko; N. V. Pasikova; N. S. Kositsyn (Neuroscience and Behavioral Physiology, 2004)

New Technologies Making Use of Sulfacrylate in Pediatric Surgery - V. T. Marchenko (Bulletin of Experimental Biology and Medicine, 2004)

Morphology of Reparative Regeneration in Organs and Tissues during Treatment with New Generation Sulfacrylate - V. T. Marchenko; V. A. Shkurupii (Bulletin of Experimental Biology and Medicine, 2004)

Structural Bases of Intracortical Processes Underlying the Synchronization of Epileptic Potentials in the Sensorimotor Areas of the Neocortex in Rats - N. V. Pasikova; V. G. Marchenko; N. S. Kositsyn (Neuroscience and Behavioral Physiology, 2001)

An improved method for isolating parts of the rat neocortex - N. V. Pasikova; V. G. Marchenko; N. S. Kositsyn (Neuroscience and Behavioral Physiology, 2000)

Dynamics of the activity of respiratory enzymes in neuronally isolated zones of the neocortex and symmetrical regions in rats - N. V. Pasikova; L. V. Nozdracheva; V. G. Marchenko; N. S. Kositsyn (Bulletin of Experimental Biology and Medicine, 1999)

Involvement of NMDA receptors in the control of respiratory rhythm generated by medullo-spinal preparations of early postnatal rats - D. V. Volgin; V. A. Marchenko; M. M. Seredenko; D. A. Vasilenko (Neurophysiology, 1998)

Effect of nitric oxide on the respiratory activity generated under hypoxic conditions by medullo-spinal preparations from early postnatal rats - D. V. Volgin; V. A. Marchenko; M. M. Seredenko (Neurophysiology, 1997)

Respiratory activity generated by semi-isolated medullo-spinal preparation and recorded from the phrenic nerve of newborn rats - V. A. Marchenko; V. B. Fenik; N. N. Preobrazhenskii; M. M. Seredenko (Neurophysiology, 1997)

Correlation between TS phenotype and pathogenicity of some animal viruses - Y. Z. Ghendon; A. T. Marchenko; S. G. Markushin; D. B. Ghenkina; A. V. Mikhejeva; E. E. Rozina (Archives of Virology, 1973)